ALTERED DISTINCTION: A CRITICAL STUDY OF THE MIND AND THE BODY IN THE CASE OF ALTERED CARBON - Kamboj, Lakshay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Altered Carbon is a Netflix original series in two parts. The First part is created by Laeta Kalogridis, and adapted from the novel, by the same title, written by Richard K. Morgan in 2001. In this Cyberpunk genre series, a new human subjectivity is represented in the series, in which a Transhuman state is imagined. In the series, human mind can be stored in ‘Cortical Stacks’ and can be transferred into changeable bodies indefinitely thereby making humans immortal. It can also be spun up in the virtual for any purpose such as interrogation, torture or a virtual meeting. Bodies can be manufactured, real or synthetic and commodified. But these capabilities also result in unfair handling and exploitation of both mind and body. Hence, this detailed content analysis will study these conflicts and issues of ‘altered carbon’ with the perspectives of the mind/body as actually distinct substances as suggested by Rene Descartes. He argues that mind and the body differ in their natures, which makes it possible for one to exist without the other. These characteristics seem to adhere to the mind/body distinction as demonstrated in the series, which will help the paper explore the problems of a Transhuman state. In conclusion, with this paper, I would be critically analyzing the altered human subjectivity and its consequences in the series.